Differences in The Level of Loneliness Experienced by Male and Female University Students During The Covid-19 Pandemic - Bagaskara, Rafli Sodiq; Mahendra, Reza; Samudra, Dhani (Faculty of Psychology, Universitas Negeri Yogyakarta, 2021)
The implementation of the physical distancing policy as an effort to prevent the transmission of the COVID-19 virus seems to have resulted in loneliness problems for students. Many studies have shown that loneliness is bad for health, such as decreased immunity and cognitive function. By knowing groups vulnerable to loneliness, appropriate preventive and curative measures can be taken. Unfortunately, few studies discuss the differences in the level of loneliness in groups of men and women. This study aims to determine whether there are differences in the level of loneliness in male and female university students during the COVID-19 pandemic. The approach used is quantitative with a comparative design. The total subjects were 192 University students consisting of 148 women (77%) and 44 men (23%). The participants were obtained using an online questionnaire through the accidental purposive sampling method. The research instrument used is the UCLA Loneliness Scale Version 3 Indonesian edition which has an alpha coefficient of 0.92. Data analysis used a different independent sample t-test. The data obtained shows that the average loneliness for men is 38,272 and for women 38,108. Based on the difference test, we obtained the following result t (190) = 0.127, p > 0.05. So it can be concluded that there is no significant difference in loneliness between male and female university students.